Approach to Reconstruction of Cheek Defects - Başağaoğlu, Berkay; Bhadkamkar, Mohin; Hollier, Pierce; Reece, Edward (Seminars in Plastic Surgery, 2018)
The cheek is the largest facial unit with a prominent position on the face. Trauma, burns, and the resection of skin cancers constitute common sources of injury, potentially resulting in defects that, through natural healing, produce noticeable scarring. Surgical repair focuses on the reformation of three-dimensional geometries, proper establishment of symmetry, and the minimization of color and texture discrepancies to the surrounding. Defects located in this region may extend to the orbital, nasal, or buccal units and cause unique structural and functional disturbances. Furthermore, without appropriate repair, full-thickness defects involving the buccal mucosa may result in oral dysfunction. In this article, the authors provide a framework to approach various cheek defects and provide a review of the host of ideologies and techniques.
Keywords: considerations of cheek reconstruction; facial flaps; skin grafting; free tissue transfer